Curved sprinting in soccer: The influence of radius - Altmann, S.; Ruf, L.; Fílter, A.; Härtel, S.; Naujoks, T.; Rauprich, M.; Seyler, C.; Baydoun, H.; Woll, A. (International Journal of Sports Science & Coaching, 2024)
The aims of this study were (i) to compare the sprint times between linear-sprint (LS) and curved-sprint (CS) tests of different radii, and (ii) to examine the relationships between sprint times in these tests in soccer players. Nineteen elite youth male soccer players (age, 18.6 ± 0.6 years) completed an LS test and three CS tests with different radii both from the left and the right side (11.15-m radius = CSwide, 9.15-m radius = CSmedium and 7.15-m radius = CSnarrow), each with a distance of 17 m. Differences in sprint times were examined using analysis of variance with Bonferroni-corrected pairwise comparisons and Cohen's d effect sizes (ES). Relationships between sprint times were determined by Pearson's product-moment correlations (r). Significantly lower sprint times were evident for LS compared to all three CS tests (p < .001, MD = 0.08-0.16 s, ES = 0.83-1.49), for CSwide compared to CSnarrow (p = .02, MD = 0.04 s, ES = 0.47) and for CSmedium compared to CSnarrow (p < .001, MD = 0.07 s, ES = 0.82). Very large correlations (p < .001, r = 0.75-0.80) were found between sprint times in LS and the three CS tests. Very large to nearly perfect correlations (p < .001, r = 0.79-0.91) were found within the three CS tests. Practitioners should be aware that sprint times are lower in LS compared to CS of different radii and that CS times are higher at narrower angles compared to wider angles. Given the high correlations within three CS tests, the application of only one CS (e.g., CSmedium) during a test battery may be sufficient if using different CS is not possible. Results of the correlation analysis also suggest that LS contributes to CS performance, however, to slightly different extents depending on the radius of the CS. Consequently, both LS and CS drills might be incorporated into sprint training practices of elite youth soccer players.